Understanding children's epistemic beliefs in elementary education. Issue 2 (4th March 2017) - Lunn Brownlee, Jo; Curtis, Elizabeth; Spooner-Lane, Rebecca; Feucht, Florian
Abstract : Research shows that the beliefs individuals hold about knowledge and knowing (epistemic beliefs) influence learning approaches and outcomes. However, little is known about the nature of children's epistemic beliefs and how best to measure these. In this pilot study, 11 Australian children (in Grade 4 or Grade 6) were asked to 'draw, write and tell' about their epistemic beliefs using drawings, written responses and interviews, respectively. Drawings were analysed, with the majority of children depicting external, one-way sources of knowledge. The written statements and interviews were analysed using inductive thematic analysis, showing that children predominantly described knowledge acquisition as processes of task-based learning. Interviews also enabled children to describe a wider range of views. These results indicate that the methodological combination of 'draw, write and tell' allowed for a deeper understanding of the children's epistemic beliefs which holds implications for future research.